Um modelo para notificações em mHealth - Costa, Adriana Cássia da (2013)
The current diversity of mobile devices with multiple functions requires that the user's attention be increasingly divided between their daily activities and notifications triggered by these devices. Whereas these notifications can generate excessive interruptions and thus be detrimental to the user's activities, it is necessary to study how to send them to reduce the annoyance of interruption of an ongoing activity, and thus diverting user attention only to the activities of their interest. Focusing on health professionals (in this case, clinicians) - who also joined the new mobile technologies at work, as a way to save time, assist in making decisions and even perform diagnostics remotely - this master s thesis aims to identify notification of these professional goals and develop a model for notifications specifically for this area (known as Mobile Health, or mHealth). In this context we developed a model for mHealth notifications based on interrupt modes as parameters Interruption, Reaction and Comprehension, and personalization of content. The model was applied in a notification system prototype and presented to user s clinicians allowing its analysis and refinement as the adequacy of the presentation settings, information types, frequency and type of proposed interruption.